STRENGTH ASSEESEMENT OF CONCRETE BY FRACTIONAL SUBSTITUTION OF THE AGGREGATE WITH GLASS POWDER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Glass powder (GP) employed in concrete creating results in greener atmosphere. In shops, broken glass sheets &flat solid cuttings square measure move to waste, that aren't recycled at the present and typically delivered to landfills for disposal. Victimization physician in concrete is a noteworthy risk for economy on waste disposal sites and conservation of atmosphere. This project examines the chance of victimization physician as fine mixture replacement in concrete. Natural sand was part replaced (0%-40%) with physician in concrete. enduringness, Compressive strength (cubes and cylinders) and Flexural strength up to twenty-eight days more matured were compared with those of high performance concrete created with natural sand.